PENGARUH WORK LIFE BALANCE TERHADAP TURNOVER INTENTION PADA GENERASI MILENIAL DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Wilson Candra Teguh Pratama; Ramlah, Sri; Aris Kusdiyanto; Widodo, Muhammad Rafi Sigit; Evelyna, Novia (MANAJEMEN DEWANTARA, 2024)
This study examines the influence of work-life balance (WLB) on turnover intention among millennials, with job satisfaction as a mediating variable. Millennials, as the dominant segment in the global workforce, often face challenges in maintaining a balance between their professional and personal lives, which can significantly impact their job satisfaction and decision to remain in an organization. Drawing on data from 350 millennial employees across various industries in Indonesia, this research employs Structural Equation Modeling (SEM) to test the relationships between WLB, job satisfaction, and turnover intention. The results reveal that work-life balance has a significant negative effect on turnover intention, with job satisfaction serving as a partial mediator. The findings suggest that when millennials perceive a better balance between their work and personal life, they are more likely to experience higher job satisfaction, which in turn reduces their intention to leave the organization. These results highlight the critical role of WLB in employee retention strategies, particularly for millennials. The study contributes to the growing body of literature on generational workforce dynamics and offers practical insights for human resource management by emphasizing the need to foster a supportive work-life balance environment to enhance job satisfaction and reduce turnover intention.